Exploring the relationship between cognitive uncertainty and home bias in financial decision-making - Liew, Guan Yen (Nanyang Technological University, 2024)
There is a lack of studies on the relationship between Cognitive Uncertainty and Home Bias. On one hand, very few papers directly elicit or quantify Cognitive Uncertainty – they instead typically anaylse Cognitive Uncertainty through a qualitative lens, or focus on conventional (general) notions of uncertainty applicable to a non-financial standpoint. On the other hand, Home Bias remains a puzzle despite extensive research on its underlying factors, with many of its associated traits unable to deliver a sharp or targeted explanation for the phenomenon. The widespread use of third party data in Home Bias research, while comprehensive, also raises issues regarding quality and difficulties in isolating individuals’ own cognitive biases. This paper aims to address these two limitations, and examine whether there is indeed a positive correlation between Cognitive Uncertainty and Home Bias. With familiarity as the key heuristic to bridge the two entities, this paper finds that individuals are indeed more cognitively uncertain in absolute valuation lotteries played on more unfamiliar countries, under a Cash Equivalent design. This, however, appears to be less of the case when considering relative valuation lotteries played under the Choice Domain design.